Curvature and Temperature Measurement Based on a Few-Mode PCF Formed M-Z-I and an Embedded FBG - Liu, H.; Yang, H.Z.; Qiao, X.G.; Wang, Y.; Liu, X.C.; Lee, Y.S.; Lim, Kok Sing; Ahmad, Harith (MDPI, 2017)
We have experimentally demonstrated an optical fiber Mach-Zehnder interferometer (MZI) structure formed by a few-mode photonic crystal fiber (PCF) for curvature measurement and inscribed a fiber Bragg grating (FBG) in the PCF for the purpose of simultaneously measuring temperature. The structure consists of a PCF sandwiched between two multi-mode fibers (MMFs). Bending experimental results show that the proposed sensor has a sensitivity of −1.03 nm/m−1 at a curvature range from 10 m−1 to 22.4 m−1, and the curvature sensitivity of the embedded FBG was −0.003 nm/m−1 . Temperature response experimental results showed that the MZI’s wavelength, λa, has a sensitivity of 60.3 pm/° C, and the FBG’s Bragg wavelength, λb, has sensitivity of 9.2 pm/° C in the temperature range of 8 to 100° C. As such, it can be used for simultaneous measurement of curvature and temperature over ranges of 10 m−1 to 22.4 m−1 and 8° C to 100° C, respectively. The results show that the embedded FBG can be a good indicator to compensate the varying ambient temperature during a curvature measurement.